PENGARUH KINERJA KEUANGAN TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN INDUSTRI TEKSTIL - Gita Afrillia Aulina; Sugeng Priyanto (Jurnal Ilmiah Manajemen dan Akuntansi, 2026)
This study aims to determine the effect of Liquidity, Solvency, Activity, and Profitability variables on Firm Value in Textile Industry Companies. The population used in this study is Textile Industry Companies listed on the Indonesia Stock Exchange with a research observation period of 2020-2024. Sample selection uses a purposive sampling method based on certain criteria adjusted to the objectives of the research problem. The number of samples used in this study was 10 from 22 companies. The data analysis technique used in this study was Multiple Linear Regression Analysis with the SPSS version 26 program tool. The results of this study indicate that solvency and activity have a positive and significant effect on firm value. While liquidity and profitability do not have a significant effect on firm value